2018
DOI: 10.3390/su10103560
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Trends of Research on New Energy Vehicle Reliability Based on the Web of Science

Abstract: In order to satisfy the increasing energy demand and deal with the environmental problem caused by the conventional energy vehicle; the new energy vehicle (NEV), especially the electric vehicle (EV), has attracted increasing attention and the corresponding research has developed rapidly in recent years. The electric vehicle requires a battery with high energy density and frequent charging. In order to ensure high performance of the electric vehicle; the reliability of its charging system is extremely important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 101 publications
(61 reference statements)
0
24
0
1
Order By: Relevance
“…In the domain of renewable energy and environment protection, the relevant literature has been not a few. For example, Xiao, et al had examined the Organic Photovoltaic Tech through text mining and knowledge visualization (Zhao, Wang, & Wang, 2018). Luo, et al analyzed the history and present of coalbed methane (CBM) in China, unearthed its variation tendency and leading institution (Luo, Zhang, Zhang, & Huang, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the domain of renewable energy and environment protection, the relevant literature has been not a few. For example, Xiao, et al had examined the Organic Photovoltaic Tech through text mining and knowledge visualization (Zhao, Wang, & Wang, 2018). Luo, et al analyzed the history and present of coalbed methane (CBM) in China, unearthed its variation tendency and leading institution (Luo, Zhang, Zhang, & Huang, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data in this paper are all collected from Clarivate Analytics' Web of Science Core Collection (WOS Core). The previous bibliometric analysis showed that the reason why WOS Core was selected is that it provides literature data with a longer time span than other databases (Zhao et al, 2018). Hence, we also chose WOS Core as the data source in this study.…”
Section: Data Retrievalmentioning
confidence: 99%
“…For the DSEG, if the eddy current, the hysteresis losses and the winding resistances are ignored, the phase voltage with no load can be expressed as (2), where u p is the voltage of p-phase. Because the turns of the field winding are much larger than the phase windings', the self-inductance of phase windings L p is much smaller than the inductance between phase windings and field winding L pf .…”
Section: Voltage Equationmentioning
confidence: 99%
“…However, because of the poor working conditions, high failure rate and short life, the generator should increase the reliability and availability continuously. For these important transportation applications, generators should have the ability to continue performing their intended functions even under phase fault [1,2]. Multiphase machines with more than three phases can be applied because they can continue to run even with one or two open-circuited phases [3].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the Web of Science (WoS) databases, Jiang et al figured out the research emphasis and development trend of urban planning for climate change from 1990 to 2016 through cluster analysis and knowledge evolution analysis using CiteSpace [17]. Zhao et al analyzed the characteristics and trends of the new energy vehicle reliability based on literature from 1998 to 2017 using CiteSpace [18]. Chen et al analyzed 3875 articles related to regenerative medicine from 2000 to 2011 using CiteSpace, finding emerging trends in this area [19].…”
Section: Introductionmentioning
confidence: 99%